If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a * 6 + 8 = 13 Reorder the terms for easier multiplication: 6a + 8 = 13 Reorder the terms: 8 + 6a = 13 Solving 8 + 6a = 13 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 6a = 13 + -8 Combine like terms: 8 + -8 = 0 0 + 6a = 13 + -8 6a = 13 + -8 Combine like terms: 13 + -8 = 5 6a = 5 Divide each side by '6'. a = 0.8333333333 Simplifying a = 0.8333333333
| 4n+73=5 | | 4x+6=-54-8 | | 3y=15-x | | -77=-++55 | | =(3-2)X+2Y+2 | | y=3.40x+2.20 | | 2x-4=86 | | ln(2x)-ln(3)=5 | | 3x+17=11x+47 | | 6x+106=2x+108 | | -2n^2+9=-7n | | =X+2Y+2 | | n-13=86 | | a^2-6a=9 | | c-28=51 | | -2x^2=-2-3x | | 35/7=p | | 3b-4/2 | | -21=9a-15-3 | | 7=g/8 | | 6b-(5-4b)=25 | | 3(x-3)+6=4x+3 | | -21=9a-15 | | 4x+2(10-x)=28 | | (a^2b^-3)^3a^2b/a(2b)^-3 | | 12x+5=5x+20 | | 12-9m=-4(-6m-3) | | x^2=11k-28 | | 4(8p-9)=-3(-12p+8) | | L=ml | | 2h+3-12h=9(-h+2) | | 12+5=7x-4 |